Prevalence of juvenile capri-paratuberculosis and geno-typing of Mycobacterium avium subspecies paratuberculosis recovered from postnatal kids - SINGH, S V; SINGH, A V; SINGH, P K; SOHAL, J S (The Indian Journal of Animal Sciences, 2011)
To investigate the prevalence of juvenile capri-paratuberculosis (JCP) in postnatal kids, 71 fecal and serum samples (30 from government and 15 from private farms and 26 from farmers’ herd) were screened by fecal culture and indigenous ELISA kit. OD values were transformed to S/P ratio and kids were categorised as: negative, suspected, low positive, positive and strong positives. Cumulatively, 69.0 and 47.8% kids were positive by ELISA and fecal culture, respectively. Individually, 73.3, 80.0 and 57.6% kids were positive by ELISA (type II sero-reactors) from government and private farms and farmers’ herd, respectively. On the other hand in culture, 40.0, 66.6 and 46.1% kids were positive from government and private farms and farmers’ herd, respectively. The isolates were primarily characterized on the basis of cultural characteristics, acid fastness, slow growth and mycobactin J dependency and were finally confirmed by specific IS900 PCR. Representative 12 MAP isolates were further genotyped using IS1311 PCR–RE analysis and all were ‘Bison type’. Study reports high prevalence (culture, 47.8% and ELISA, 69.0%) of MAP, and ‘Bison type’ was predominant geno-type in young kids from farm and farmer’s herds. Potential of indigenous ELISA kit for the diagnosis of JCP has been discussed.